ANALYSIS OF FINANCIAL PERFORMANCE USING PEARLS AT THE THANKS TO BULUKUMBA SAVINGS AND LOANS COOPERATIVE 2018-2022 - Yuan Swastika; M. Tahir, An Najar (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2024)
In a Savings and Loan Cooperative, good management of protection, effective financial structure, asset quality, rates of return and costs, liquidity, and signs of growth are key factors that support long-term success. The theories put forward by the experts above provide an important basis for cooperative management to understand and implement appropriate strategies in maintaining the sustainability and growth of cooperatives. This research aims to analyze the financial performance of the Thanks to Bulukumba Savings and Loans Cooperative (KSP) during the 2018-2022 period using the PEARLS method. The PEARLS method consists of aspects of Protection, Effective Financial Structure, Asset Quality, Rates of Return and Costs, Liquidity, and Signs of Growth. The research results show that even though KSP Berkat experiences fluctuations in several indicators, overall the cooperative remains in the healthy category. This evaluation provides an important picture of the cooperative's strengths and weaknesses for better strategic planning in the future.